2003
DOI: 10.1007/s00049-003-0238-0
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and chemical characterization of egg surface of honeybee worker and queen-laid eggs

Abstract: Worker policing in honeybees predicts the evolution of a mechanism to discriminate between queenand worker-born eggs. Although it has been postulated that this discrimination is based on an egg recognition pheromone, neither the chemistry nor the glandular source were elucidated. To verify whether egg discrimination might be based on structural differences, we compared the ultrastructure surface of queen-laid diploid and haploid eggs to that of worker-laid eggs using SEM. Only small differences between the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…In the honey bee A. mellifera, worker policing of eggs occurs as well (52); this has led to a number of studies of the compounds found on queenand worker-laid eggs and the compounds present in the queen's Dufour's gland (53) and in egg-laying workers (54)(55)(56), which appear to mimic queen specific profiles. Although there is experimental evidence that the egg identification cue originates from Dufour's gland secretions (57), behavioral experiments have failed so far to show which of the many compounds are active (58)(59)(60), and it appears that in this case hydrocarbons are not involved (58).…”
Section: Discussionmentioning
confidence: 99%
“…In the honey bee A. mellifera, worker policing of eggs occurs as well (52); this has led to a number of studies of the compounds found on queenand worker-laid eggs and the compounds present in the queen's Dufour's gland (53) and in egg-laying workers (54)(55)(56), which appear to mimic queen specific profiles. Although there is experimental evidence that the egg identification cue originates from Dufour's gland secretions (57), behavioral experiments have failed so far to show which of the many compounds are active (58)(59)(60), and it appears that in this case hydrocarbons are not involved (58).…”
Section: Discussionmentioning
confidence: 99%
“…Workers probably establish the source of an egg on the basis of substances that are deposited on the egg's surface when it is laid (Katzav-Gozansky et al, 2001). The queen's eggs have a more complex hydrocarbon coating than worker-laid eggs, and acetates of fatty alcohols, alkenes, and monomethylalkanes are characteristic to eggs that are laid by a queen (Katzav-Gozansky et al, 2003).…”
Section: Killing Of Developing Brood-mentioning
confidence: 99%
“…To date, although several studies have examined morphological change (2,26,27) and gene expression (25,28,29) during the period of embryogenesis in the honey bee, only a few works report on the preliminary results of the unraveling molecular underpinnings of worker (30) and drone (31) embryogenesis at the proteomic level, identifying only 107 proteins. MS-based proteomics is the primary technology that enables a system-wide view of proteomes and their changes.…”
mentioning
confidence: 99%